2018
DOI: 10.3928/19404921-20180322-01
|View full text |Cite
|
Sign up to set email alerts
|

Early Readmission Risk Identification for Hospitalized Older Adults With Decompensated Heart Failure

Abstract: The current study evaluated risk factors of early hospital readmission in geriatric patients with acute heart failure (HF) and analyzed 2,279 consecutively hospitalized older adults with decompensated HF from November 2013 to October 2014 across 15 U.S. hospitals. The eTracker-HF was designed to make risk factors known to treating clinicians in electronic health records. Multilevel multivariate logistic regression was applied to examine the association between risk factors and all-cause and HF 30-day readmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
0
14
2
Order By: Relevance
“…More than 1 patient over 4 were readmitted to the hospital in our study population after 30 days. Our readmission rate was more frequent than those observed in some previous studies (37)(38)(39) over the same follow-up time, yet the discrepancies could be explained by the age of the patients (much older in our population than in the others (37)(38)(39), high comorbidity burden (which was evaluated in our study, whether not entirely specified in other ones), and in line with Molvin et al who observed a 33.5% readmission rate, in a Swedish cohort of 268 patients (mean age 75 years) over a follow-up time of 5 months (40).…”
Section: Discussioncontrasting
confidence: 60%
“…More than 1 patient over 4 were readmitted to the hospital in our study population after 30 days. Our readmission rate was more frequent than those observed in some previous studies (37)(38)(39) over the same follow-up time, yet the discrepancies could be explained by the age of the patients (much older in our population than in the others (37)(38)(39), high comorbidity burden (which was evaluated in our study, whether not entirely specified in other ones), and in line with Molvin et al who observed a 33.5% readmission rate, in a Swedish cohort of 268 patients (mean age 75 years) over a follow-up time of 5 months (40).…”
Section: Discussioncontrasting
confidence: 60%
“…The readmission rate in our study for Chinese senile patients with acute decompensated heart failure was 33.55%, much higher than that as reported by other researchers which ranges from16.8% [6]to 32.6% [7]. Since heart failure has an overwhelming prevalence among senile groups, meanwhile old age is also a risk factor for readmission.…”
Section: Discussioncontrasting
confidence: 58%
“…The unscheduled readmission rate was defined as the rate of the emergency visit and the unscheduled rehospitalization within 12 weeks of intervention to evaluate the chronic disease progression (Ayatollahi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%